The Russian opera libretto as preached and practiced in the nineteenth century - Frainier, M (2021)
This thesis analyses the formal qualities of the nineteenth-century Russian opera libretto and its status as neither a literary nor musical object in order to consider broader questions that can help rethink how to write the history of Russian opera. Such questions include the nature of operatic authorship, collaborative partnerships during the creation of the libretto, the use of Western European models and forms in Russian opera, and the use of anthropological or folkloric sources. I use four specific case studies drawn from across the century, allowing the development of these broader questions to be traced over roughly ninety years of Russian cultural history. Building on existing interdisciplinary scholarship on Russian opera, this thesis seeks to argue that scholars need to look beyond a prevalent ‘page-to-stage’ model of operatic adaptation and explore instead a more multifocal and collaborative approach to the history of Russian opera and its relationship to literature.